Multichannel adaptive deployment and reliable communication design for unmanned surface vessel. (23rd January 2020) - Yin, Qiyu; Lv, Yuezu
For the unmanned surface vessel in performing military missions, the safety and controllability are two basic requirements, which need reachable communication channel and reliable data transmission. This article proposes an adaptive switching model with multichannel resource and the unmanned surface vessel shore-to-sea data intercommunication design method. The scheme adopts various mechanisms such as data space, standardized encapsulation, numbering and verification, and active/passive retransmission, which can ensure reliable data transmission and provide reliable communication information for unmanned surface vessel during autonomous mission. A sea trial is also carried out on the unmanned surface vessel control system based on the design scheme. Data analysis shows that the system can successfully realize communication switching and continuous data transformation, which is consistent with design expectation, and guarantees the continuous monitoring and control of unmanned surface vessel by shore-based control station.